ANALISIS TARIF BERDASARKAN BIAYA OPERASIONAL KENDARAAN DAN PENDEKATAN ATP–WTP (STUDI KASUS: FEEDER LRT MUSI PALEMBANG) - Khanza, Ayu Kamila; Michael, Michael; Elian Zhafira; Putri Ayu Dwiyana; Cahyo Agung Saputra; Tiorivaldi, Tiorivaldi (Yayasan Nusantara Hasana Berdikari, 2026)
The LRT Feeder is a supporting mode of transportation that connects areas not yet served by major transport systems to service hubs such as stations. This study aims to analyze the relationship between Vehicle Operating Costs (BOK), Ability to Pay (ATP), and Willingness to Pay (WTP) in determining the fare for the Musi Palembang LRT Feeder on Corridor II. A descriptive quantitative approach was used, with data collected through questionnaires distributed to 100 respondents. Calculations followed the guidelines of the Ministry of Transportation Regulation KM 251 Year 2022. The results show that the BOK is Rp616.64, ATP is Rp158.30, and WTP is Rp130.47. The fact that ATP is higher than WTP but still far below BOK indicates that users have the financial capacity to pay but are not yet able to fully cover operational costs, and their willingness to pay remains low. Determining an ideal fare should consider improving service quality or implementing subsidy interventions to bridge the cost gap and ensure service sustainability. Further research can examine an appropriate fare scheme for users.